If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(a + 2) = -10 Reorder the terms: -8(2 + a) = -10 (2 * -8 + a * -8) = -10 (-16 + -8a) = -10 Solving -16 + -8a = -10 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -8a = -10 + 16 Combine like terms: -16 + 16 = 0 0 + -8a = -10 + 16 -8a = -10 + 16 Combine like terms: -10 + 16 = 6 -8a = 6 Divide each side by '-8'. a = -0.75 Simplifying a = -0.75
| 20y+2=10 | | 3w+7x-10+2y=8w-9x-16 | | -7x+2=-19 | | -5-(15y-1)=2(7y-16-y) | | 5y-13=6(y+3) | | 5p+5=4p+14 | | 2y(2y+3)=6y(y-1) | | 18*(25*10)=330x | | 125=-5p-5(3+6p) | | 18*(25*10)=330 | | 8z=3x+5x | | -2(x-7)=4(x-2) | | ax-4=9 | | 4+7x-12=4x+12-x | | (q-8)=7q+5 | | -2x-12+3=3+x | | x*x+4y=(x+6)(x-2) | | 3x+3=-2(x-5) | | x^2+y^2+4xy+42x=0 | | 5x+20=3x-50 | | 6xy+xy= | | 2x+3x=20-2x | | 3x+20=5x+50 | | 3y-3x=10 | | N+3*5=3*2n-1 | | f(x)=x^2+y^2+4xy+42x | | -2n-5(n-6)=9 | | 8y-(2y-3)=9y+12 | | 3x^4-x+6=0 | | m=7-3(p-m) | | 52x+7=57 | | 3k/5+44=12k/25+18 |